Manipulation of the sodium‐potassium ratio as a lever for controlling cell growth and improving cell specific productivity in perfusion CHO cell cultures. Issue 4 (22nd January 2018) - Wang, Samantha B.; Lee‐Goldman, Alexandria; Ravikrishnan, Janani; Zheng, Lili; Lin, Henry
Abstract: Perfusion processes typically require removal of a continuous or semi‐continuous volume of cell culture in order to maintain a desired target cell density. For fast growing cell lines, the product loss from this stream can be upwards of 35%, significantly reducing the overall process yield. As volume removed is directly proportional to cell growth, the ability to modulate growth during perfusion cell culture production thus becomes crucial. Leveraging existing media components to achieve such control without introducing additional supplements is most desirable because it decreases process complexity and eliminates safety and clearance concerns. Here, the impact of extracellular concentrations of sodium (Na) and potassium (K) on cell growth and productivity is explored. High throughput small‐scale models of perfusion revealed Na:K ratios below 1 can significantly suppress cell growth by inducing cell cycle arrest in the G0/1 phase. A concomitant increase in cell specific productivity was also observed, reaching as high as 115 pg/cell/day for one cell line studied. Multiple recombinant Chinese hamster ovary (CHO) cell lines demonstrated similar responses to lower Na:K media, indicating the universal applicability of such an approach. Product quality attributes were also assessed and revealed that effects were cell line specific, and can be acceptable or manageable depending on the phase of the drug development. Drastically altering Na and K levels in perfusion media as a lever to impact cell growth and productivity is proposed. Abstract : Contour plots of different sodium and potassium ratios in perfusion medium reveal higher levels of potassium decrease cell growth and significantly increase CHO cell production of recombinant protein.